Method for reducing barium salt by barite calcination method
By using ZnO and/or FeSO4 as mineralizers in barite carbothermal reduction method and combining CaCO3 flux to optimize raw material ratio and particle size, the problems of low conversion rate, high energy consumption and large sulfur dioxide emissions in barite carbothermal reduction method are solved, and efficient and clean barium salt production is achieved.
Patent Information
- Application Number
- CN202510635412.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-16
- Publication Date
- 2025-08-08
AI Technical Summary
In the existing barite carbon-thermal reduction method, the conversion rate is low, the slag production is large, the energy consumption is high, and the sulfur dioxide emission is high. The existing technology does not fully consider the impact of raw material components on the reaction, resulting in incomplete reactions and environmental pollution problems.
ZnO and/or FeSO4 are used as mineralizers and CaCO3 is used as flux to treat barite ore by calcining at 900-1100°C for 60-90 minutes, optimizing raw material ratio and fine particle size design, improving reaction activity and reducing sulfur dioxide emissions.
It significantly improves the conversion rate of barium salt, reduces energy consumption and sulfur dioxide emissions, produces purer barium salt products, reduces by-products, and achieves a cleaner and efficient reduction process.
Smart Images

Figure CN120440844A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical industry, relates to the smelting treatment of barite ore, and particularly relates to a method for reducing barium salt by a barite calcination method. Background Art
[0002] Barite is a common barium-containing mineral in nature. Its main component is barium sulfate (BaSO4). It is a non-metallic mineral resource with a mineral composition of BaO (65.7% by weight) and SO3 (34.3% by weight).
[0003] The barite carbothermal reduction process is essentially a phase transition process in which BaSO4 is converted to BaS. However, existing technologies mostly use high-purity barite as raw material, without fully considering the influence of raw material composition on the barite carbothermal reduction reaction. In the actual reaction process, since barite is a non-metallic mixed mineral product mainly composed of barium sulfate (BaSO4), it is often accompanied by gangue minerals such as quartz, clay, sericite, and limonite. Each mineral component undergoes a complex solid-phase reaction process with multi-component and multi-phase participation during the high-temperature carbothermal reduction process. The mutual restriction or mutual promotion of various reactions may affect the transformation of the BaSO4 phase to the BaS phase in the system. At the same time, the current carbothermal reduction method using carbon as a reducing agent has many side reactions. The existing technology mainly focuses on the influence of process conditions on the conversion rate of barium sulfide. There is a clear lack of research on the phase transition process of barite carbothermal reduction and the laws of mineral phase change. In particular, there are few research reports on the phase transition behavior and regulation mechanism of gangue minerals in barite.
[0004] In general, the existing barium salt preparation technology mainly has problems such as low conversion rate, large slag production, and high production energy consumption.
[0005] For example, patent CN118125383A discloses a method for increasing barium sulfide production using limestone and pyrite. By adding limestone and pyrite, this method effectively consumes silica during the reaction, reducing the amount of silica reacting with barium sulfide and increasing barium sulfide production. While the use of pyrite as a reducing agent in the reaction aids the reduction process and can assist in impurity removal, the use of pyrite can result in higher sulfur dioxide emissions, which is detrimental to environmental protection. Summary of the Invention
[0006] In order to overcome the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a method for reducing barium salts by calcining barite, so as to improve the BaS conversion rate while reducing energy consumption and reducing pollutant emissions.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for reducing barium salt by calcining barite comprises mixing barite ore, coal powder and a mineralizer, calcining at 900-1100° C. for 60-90 minutes, and cooling to obtain barium salt (BaS); wherein the mineralizer is ZnO and / or FeSO4.
[0009] In one embodiment, the amount of the coal powder added is 20-30% by weight of the barite ore, and the amount of the mineralizer added is 0.05-0.1% by weight of the barite ore.
[0010] In one embodiment, the mineralizer is ZnO, and the weight ratio of barite ore, coal powder and mineralizer is 100:26:0.1.
[0011] In one embodiment, the mineralizer is FeSO4, and the weight ratio of barite ore, coal powder and mineralizer is 100:26:0.1.
[0012] In one embodiment, CaCO3 is further added during the mixing.
[0013] In one embodiment, the amount of CaCO3 added is 0.05-0.1% by weight of the barite ore.
[0014] In one embodiment, the mineralizer is ZnO, and the weight ratio of barite ore, coal powder, mineralizer and CaCO3 is 100:26:0.05:0.05, or 100:26:0.1:0.1.
[0015] In one embodiment, the mineralizer is FeSO4, and the weight ratio of barite ore, coal powder, mineralizer and CaCO3 is 100:26:0.1:0.1.
[0016] In one embodiment, before or after mixing, the mixture is pulverized to a size of 200 mesh.
[0017] Compared with the prior art, the present invention can effectively reduce sulfur dioxide emissions by adding ZnO and / or FeSO4 to enhance the reduction process, and improve the conversion rate of barite to produce barium salts by combining the raw material ratio and fine particle size design.
[0018] Specifically, the present invention adds ZnO during the reduction process, which acts as a mineralizer to lower the reaction temperature and also helps promote the conversion of barium sulfate into barium sulfide. In the prior art, the choice of flux is not optimally utilized, resulting in higher reaction temperatures or incomplete reduction. The present invention solves these problems by specifically selecting zinc oxide (ZnO), reducing energy requirements and improving reaction efficiency. Zinc oxide (ZnO) also helps remove impurities by reacting with impurities such as silica to form easily separable compounds. The resulting beneficial effects include reduced energy consumption, a cleaner reaction, and improved purity of the final barium salt product.
[0019] In the prior art, the use of mineralizers may be inefficient or uncontrolled, which may lead to high sulfur dioxide emissions and be detrimental to environmental protection. The present invention introduces a controllable iron source by selecting ferrous sulfate (FeSO4), which can effectively serve as a mineralizer. Ferrous sulfate (FeSO4) not only helps to reduce barium sulfate, making the reaction cleaner, but also helps to remove impurities such as sulfur from the system. Compared with other mineralizers that may cause the formation of undesirable by-products, ferrous sulfate (FeSO4) provides a more controlled and efficient reduction process. The beneficial effects achieved by using ferrous sulfate (FeSO4) include improved reaction control, a cleaner reaction, higher purity of barium sulfide, and fewer by-products. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION
[0021] The embodiments of the present invention are described in detail below with reference to the accompanying drawings and examples.
[0022] like Figure 1 As shown, the present invention is based on the carbothermal reduction method, selects ZnO or FeSO4 as a mineralizer, and CaCO3 as a selectively added flux to participate in the reduction reaction, effectively treats silicon dioxide, and improves the purity of the produced barium salt. The main steps are as follows:
[0023] 1. Raw material pretreatment.
[0024] The raw materials of the present invention are barite ore, coal powder, ZnO and / or FeSO4, CaCO3 (optionally added). The raw materials are crushed to 200 mesh and then mixed, or crushed to 200 mesh after mixing.
[0025] By selecting ZnO and / or FeSO4 as mineralizers, the present invention can significantly enhance the reduction reaction process, improve reaction activity and efficiency, effectively reduce sulfur dioxide emissions, and reduce the time and energy required for the process.
[0026] Specifically, ZnO acts as a mineralizer, lowering the melting point of the mixture and aiding the reduction process. It also reacts with BaSO₄ during the reduction reaction. FeSO₄ acts as a mineralizer and provides iron, aiding the reduction process. It also forms iron oxides, which react with SiO₂ to form iron silicate, assisting in impurity removal.
[0027] The present invention uses CaCO3 to help bind impurities, improve the quality of the final BaS product, and ensure a purer product with fewer contaminants. Specifically, CaCO3, as a flux, can decompose to form CaO and CO2. CaO can react with SiO2 to form calcium silicate (CaCO3), thereby facilitating the purification of the product.
[0028] Thus, the present invention treats silicon dioxide (which is present as an impurity in barite) by forming compounds such as calcium silicate and iron silicate, and improves the purity of the produced barium salt.
[0029] The barite ore referred to in this invention typically contains barium sulfate (BaSO4), but may also contain various impurities such as silicon dioxide (SiO2), ferric oxide (Fe2O3), and trace elements. Ores with higher SiO2 content may require more CaCO3 and FeSO4 to effectively remove impurities. In this invention, existing testing and characterization indicate that the barite raw material used is primarily BaSO4, with a very small amount of CaSO4.
[0030] The coal powder used in this invention is preferably fine-particle, high-calorific value, and controlled sulfur content to optimize the reduction reaction. Smaller coal particles increase surface area, thereby improving reaction efficiency. Sulfur content is particularly important, as excessive sulfur can lead to the formation of unwanted byproducts during calcination. In this invention, the coal powder used has a 1:1 coal:coke foam ratio and contains 70.11% fixed carbon.
[0031] In traditional methods, raw materials are usually not ground finely enough, resulting in low reaction rate and incomplete reduction of barium sulfate. The present invention achieves a fine but balanced particle size by crushing each raw material, especially barite ore, to 200 mesh (about 74 μm), ensuring that the particle distribution is finer and more uniform, significantly increasing the surface area of the reaction, enhancing the reaction efficiency, and allowing barium sulfate to be converted into barium sulfide more completely and faster. This finer particle size helps to overcome the limitations of the slower reaction kinetics in the background art, wherein larger particle sizes may lead to incomplete reactions or impurities in the final product. The beneficial effect of this step is to increase the yield and purity of the barium salt and reduce energy consumption due to the accelerated reaction rate. Specifically, its principles include:
[0032] 1) Enhanced Reactivity: Crushing to a fine mesh increases the specific surface area of the barite particles, which enhances the reactivity during the reduction process. This allows for more efficient gas-solid interactions, resulting in a more complete reduction of the barite.
[0033] 2) Optimized particle size: Particles that are too small can cause problems such as sintering and sticking to the furnace wall. 200 mesh strikes a balance between being small enough to increase reactivity and large enough to avoid severe sintering. This mesh size ensures that the particles are not too fine to stick to the furnace wall or be carried away by the exhaust gas.
[0034] 3) Improved flow and mixing: By crushing to 200 mesh, the barite particles remain a size that supports better flow and mixing in the furnace. This reduces the possibility of fine particles being trapped in the material flow, avoiding incomplete reaction.
[0035] 4) Reduced material loss: Compared with very fine particles (e.g., less than 10 μm), fine particles crushed to 200 mesh are less likely to be carried away by exhaust gas. This helps to minimize material loss during processing.
[0036] 2. Proportion of ingredients and thorough mixing.
[0037] Barite ore, coal powder, ZnO and / or FeSO4, CaCO3 (optional addition) are fully mixed in a certain proportion.
[0038] In the present invention, the optimal ratio is: 100 parts by weight of barite ore; 20-30 parts by weight of coal powder, which is mainly used as a reducing agent; 0.05-0.1 parts by weight of ZnO and / or FeSO4, which are used as mineralizers to promote the reduction reaction; 0.05-0.1 parts by weight of CaCO3, which is used to bind impurities and improve product quality.
[0039] The present invention combines the optimized raw material ratio and fine particle size to improve the conversion rate of barite to produce barium salts and minimize problems such as sintering and material adhesion to the furnace wall. This makes the material use more efficient and reduces operational problems.
[0040] 3. Calcination.
[0041] The fully mixed materials are placed in a muffle furnace and calcined at 900-1100°C for 60-90 minutes.
[0042] The calcination temperature and reaction time selected in the present invention can maximize the BaS conversion rate. The reactions that may occur during the process include:
[0043] 1) Coal powder reduces barite.
[0044] BaSO4+4C→BaS+4CO
[0045] In this process, barite reacts with carbon to produce barium sulfide and carbon monoxide.
[0046] 2) Pyrite (FeS2) reduction of barite (BaSO4)
[0047] 4BaSO4+4FeS2+4C→4BaS+4FeS+4CO2
[0048] Barite reacts with pyrite and carbon to produce barium sulfide, iron sulfide and carbon dioxide.
[0049] 3) BaSO4 reduces barite.
[0050] BaSO4+2FeSO4+4C→BaS+2FeS+4CO2
[0051] Barite reacts with ferrous sulfate and carbon to produce barium sulfide, iron sulfide and carbon dioxide.
[0052] 4) ZnO reduces barite.
[0053] BaSO4+2ZnO+4C→BaS+2Zn+4CO2
[0054] Barite reacts with zinc oxide and carbon to produce barium sulfide, zinc and carbon dioxide.
[0055] 5)Decomposition and reaction of CaCO3.
[0056] CaCO3→CaO+CO2
[0057] Calcium carbonate decomposes into calcium oxide and carbon dioxide during heating.
[0058] CaO+SO2+1 / 2O2→CaSO4
[0059] Calcium oxide reacts with sulfur dioxide and oxygen to form calcium sulfate, which helps bind impurities.
[0060] The muffle furnace of the present invention is of electric heating type.
[0061] 4. Cool down.
[0062] The mixture was naturally cooled to room temperature to obtain barite clinker, i.e., the barium salt of the present invention. The BaS conversion rate and the acid-soluble barium conversion rate were calculated according to the national standard JC / T1021.7-2007.
[0063] Experimental and calculation results show that the BaS conversion rate of the present invention is always maintained above 75%, with a maximum of 81.01%. In addition, through the above-mentioned means, the present invention can reduce emissions and waste, and is more environmentally friendly.
[0064] The zinc oxide (ZnO), calcium carbonate (CaCO3), and ferrous sulfate (FeSO4) used in the present invention have multiple functions: zinc oxide (ZnO) and ferrous sulfate (FeSO4) primarily serve as mineralizers, forming a eutectic with the reactants, allowing the solid reactants to form a liquid phase at a lower temperature, accelerating the diffusion effect on the solid phase, helping to control the reaction temperature, and improving the efficiency of the reduction process. Furthermore, calcium carbonate (CaCO3) and ferrous sulfate (FeSO4) help remove unwanted impurities, particularly silicon dioxide (SiO2), by forming compounds such as calcium silicate (CaSiO3) and ferrosilicate, which are easily separated from the final product.
[0065] The advantages of this method are the higher purity of the barium salt produced and the improved process efficiency. By using these compounds, the reaction becomes more controllable, resulting in a higher yield of barium sulfide and fewer by-products. In addition, this method has the potential to reduce energy consumption by lowering the temperature required for the reduction reaction, making it more cost-effective and environmentally friendly than traditional methods. In summary, the main difference lies in the addition of specific mineralizers and fluxes, which not only promote the reduction of barium sulfate but also improve the efficiency and purity of the entire process. The advantages are more controlled reaction conditions, cleaner reactions, reduced impurities and potentially lower energy consumption.
[0066] The following are several specific embodiments of the present invention, which can better illustrate the effects of the present invention in combination with the embodiments.
[0067] Example 1
[0068] Barite ore, coal powder, and ZnO were ground to 200 mesh. 100 g of the ground barite ore, 26 g of coal powder, and 0.1 g of ZnO were mixed thoroughly and then placed in a muffle furnace and calcined at 1100°C for 90 minutes. The mixture was cooled naturally to room temperature to obtain barite clinker A1.
[0069] Example 2
[0070] Barite ore, coal powder, and ZnO were separately crushed to 200 mesh. 100 g of barite ore powder, 26 g of coal powder, 0.05 g of ZnO, and 0.05 g of CaCO₃ were thoroughly mixed and then placed in a muffle furnace and calcined at 1100°C for 90 minutes. The mixture was then cooled naturally to room temperature to obtain barite clinker A2.
[0071] Example 3
[0072] Barite ore powder, coal powder, and ZnO were separately crushed to 200 mesh. 100g of barite ore powder, 26g of coal powder, 0.1g of ZnO, and 0.1g of CaCO3 were thoroughly mixed and then placed in a muffle furnace and calcined at 1100°C for 90 minutes. The mixture was then cooled naturally to room temperature to obtain barite clinker A3.
[0073] Example 4
[0074] Barite powder, coal powder, and FeSO4 were ground to 200 mesh. 100 g of barite powder, 26 g of coal powder, and 0.1 g of FeSO4 were mixed thoroughly and then placed in a muffle furnace for calcination at 1100°C for 90 minutes. The mixture was then cooled naturally to room temperature to obtain barite clinker A4.
[0075] Example 5
[0076] Barite ore powder, coal powder, and FeSO4 were separately ground to 200 mesh. 100g of barite ore powder, 26g of coal powder, 0.1g of FeSO4, and 0.1g of CaCO3 were thoroughly mixed. The mixture was then placed in a muffle furnace and calcined at 1100°C for 90 minutes. The mixture was then cooled naturally to room temperature to obtain barite clinker A5.
[0077] Example 6
[0078] Barite ore powder, coal powder, FeSO4, and ZnO were separately ground to 200 mesh. 100 g of barite ore powder, 26 g of coal powder, 0.05 g of FeSO4, and 0.05 g of ZnO were thoroughly mixed and then placed in a muffle furnace and calcined at 1100°C for 90 minutes. The mixture was then cooled naturally to room temperature to obtain barite clinker A6.
[0079] Example 7
[0080] Barite ore powder, coal powder, FeSO4, and ZnO were separately ground to 200 mesh. 100 g of barite ore powder, 26 g of coal powder, 0.05 g of FeSO4, 0.05 g of ZnO, and 0.1 g of CaCO3 were thoroughly mixed and then placed in a muffle furnace and calcined at 1100°C for 90 minutes. The mixture was naturally cooled to room temperature to obtain barite clinker A7.
[0081] The raw material components of the above seven groups of embodiments are as follows:
[0082]
[0083]
[0084] The barite clinker A1, A2, A3, A4, A5, A6, and A7 obtained in the seven groups of examples above were immersed in hot water at a material-liquid ratio of 1:15 (volume ratio), placed in a water bath at 90°C and stirred for 4 hours, filtered, and the filtration residue was barium slag. The filtrate was diluted to volume in a 250mL volumetric flask. The filtrate was the BaS solution. Referring to the standard JC / T 1021.7-2007, 100mL of the BaS solution was placed in a 250mL beaker, 1 drop of methyl orange solution (1g / L) was added, and hydrochloric acid was added until it just turned red and an excess of 2mL was added. Water was added in an appropriate amount, heated to a boil, and about 10mL of concentrated H2SO4 was added. After slightly boiling for about 5 minutes, it was allowed to stand overnight. The filtrate was filtered with quantitative filter paper, and the precipitate was washed with 0.05mol / LH2SO4 until it was free of Cl. - , put the precipitate and filter paper into a constant weight porcelain crucible, place it in a high temperature furnace for ashing to constant weight, cool and weigh, and the BaS conversion rate is calculated as follows:
[0085]
[0086] ω (BaS) is the BaS conversion rate, %; m1 is the mass of the crucible plus precipitate, in grams (g); m2 is the mass of the empty crucible, in grams (g); V s is the total volume of the test solution, in milliliters (mL); m s is the mass of barite raw material, in grams (g); is the mass fraction of BaSO4 in the barite raw material, expressed in %; V1 is the volume of the test solution taken, in milliliters (mL).
[0087] The conversion rate of BaS (water-soluble barium) (i.e., the yield of BaS) was determined as shown in Table 1. As can be seen from Table 1, the conversion rate of BaS in the present invention reached above 75%, among which Example 4 had the highest conversion rate of 81.01%.
[0088] Table 1 Conversion rate data of sample BaS
[0089]
[0090]
[0091] After hot water leaching of the barite clinker, filter the resulting residue (i.e., the barium residue from the previous step) and dissolve it in hydrochloric acid (commercially available concentrated hydrochloric acid, undiluted). Heat and boil for 30 minutes (using a reflux condenser and a balloon). Cool, filter, and dilute to volume. The filtrate is the acid-soluble barium solution. Referring to standard JC / T 1021.7-2007, the acid-soluble barium conversion rate is calculated as follows:
[0092]
[0093] ω(酸溶钡) is the conversion rate of acid-soluble barium, %; m1 is the mass of the crucible plus precipitate, in grams (g); m2 is the mass of the empty crucible, in grams (g); V s is the total volume of the test solution, in milliliters (mL); m s is the mass of barite raw material, in grams (g); is the mass fraction of BaSO4 in the barite raw material, the value is expressed in %; V1 is the volume of the test solution taken, the unit is milliliter (mL).
[0094] The data of the acid-soluble barium conversion rate are shown in Table 2 below.
[0095] Table 2 Sample acid-soluble barium conversion rate data
[0096]
[0097] In summary, the present invention addresses the problems of incomplete reaction, high energy consumption, unclean reaction, and impurity formation in the prior art by grinding the raw materials to 200 mesh, selecting zinc oxide and ferrous sulfate, and optimizing the raw material ratios. By overcoming these drawbacks, the present invention achieves beneficial effects such as higher final product purity, improved reaction efficiency, and reduced environmental impact. The careful selection of raw materials and their ratios results in a more controllable and efficient reduction process, representing a significant improvement over traditional methods.
Claims
1. A method for reducing barium salts by calcining barite, characterized in that: Barite ore, coal powder and mineralizer are mixed, calcined at 900-1100° C. for 60-90 minutes, and cooled to obtain barium salt; wherein the mineralizer is ZnO and / or FeSO 4 .
2. The method for reducing barium salt by calcining barite according to claim 1, characterized in that By weight, the added amount of the coal powder is 20-30% of the barite ore, and the added amount of the mineralizer is 0.05-0.1% of the barite ore.
3. The method for reducing barium salt by calcining barite according to claim 1, characterized in that The mineralizer is ZnO, and the weight ratio of barite ore, coal powder and mineralizer is 100:26:0.
1.
4. The method for reducing barium salt by calcining barite according to claim 1, characterized in that The mineralizer is FeSO4, and the weight ratio of barite ore, coal powder and mineralizer is 100:26:0.
1.
5. The method for reducing barium salt by calcining barite according to claim 1, characterized in that: During the mixing, CaCO3 is also added.
6. The method for reducing barium salt by calcining barite according to claim 5, characterized in that: The amount of CaCO3 added is 0.05 to 0.1% by weight of the barite ore.
7. The method for reducing barium salt by calcining barite according to claim 5, characterized in that: The mineralizer is ZnO, and the weight ratio of barite ore, coal powder, mineralizer and CaCO3 is 100:26:0.05:0.05, or 100:26:0.1:0.
1.
8. The method for reducing barium salt by calcining barite according to claim 5, characterized in that: The mineralizer is FeSO4, and the weight ratio of barite ore, coal powder, mineralizer and CaCO3 is 100:26:0.1:0.
1.
9. The method for reducing barium salt by calcining barite according to any one of claims 1 to 8, characterized in that: Before or after mixing, the mixture is pulverized to 200 mesh.